Порівняння резонаторних та хвилевідних датчиків в НВЧ діагностиці - Бойко, Б. Ю. (ХНУРЕ, 2021)
The report discusses the results of a numerical study of the electrodynamic properties of waveguide and resonator microwave sensors. It is shown that the achievable field strength in an object when using a resonator probe is an order of magnitude higher compared to a similar waveguide sensor. It has been established that the use of resonator sensors is more preferable because of the greater sensitivity, which is achieved by a much higher energy of the electromagnetic field concentrated in the resonator volume and in the object under study. Quantitative data are presented, convincing of the clear advantage of using resonator sensors in local microwave diagnostics.
Keywords: резонатор; НВЧ діагностика